105k views
3 votes
What is 3+7x-(2+9x)

User Rob Allen
by
6.1k points

2 Answers

4 votes

3+7x-(2+9x)=x

We simplify the equation to the form, which is simple to understand

3+7x-(2+9x)=x

Remove unnecessary parentheses

3+7x-2-9x=x

We move all terms containing x to the left and all other terms to the right.

+7x-9x-1x=-3+2

We simplify left and right side of the equation.

-3x=-1

We divide both sides of the equation by -3 to get x.

x=0.33333333333333

User MorningGlory
by
6.0k points
0 votes

3 + 7x -(2 + 9x)

3 + 7x - 2 - 9x

3 - 2 + 7x - 9x

1 + 7x - 9x

1 - 2x

User Asara
by
5.9k points